Calculation of a conversion factor for estimating the glycolytic contribution in exercise from post-exercise blood lactate concentration - Hill, David W.; Mihalek, John Michael (Frontiers in Physiology, 2024)
The study of the energetics of exercise is vitally important. While there is considerable ongoing research about the aerobic contribution, most of our current knowledge about the measurement of the glycolytic portion of the anaerobic contribution during exercise is based on research from the sixties to eighties of the last century. The glycolytic contribution is often estimated based on post-exercise blood lactate concentrations, but only one study has attempted to determine the value of the conversion factor without making a number of assumptions in the original 1933 study (Gladden and Welch, 1978). Effective sample size in that one study was N = 4. In the present study, we do not rely on the original assumptions. Rather, we have directly calculated the value of the conversion factor as the ratio between the increase in glycolytic contribution engendered by exercising in hypoxia and the related increase in blood lactate concentration. We believe that it is important to have a validated conversion factor to use in the estimation of the anaerobic contribution in exercise.